EphrinB2 sharpens lateral motor column division in the developing spinal cord. Issue 1 (December 2015) - Luxey, Maëva; Laussu, Julien; Davy, Alice
Abstract Background During sensori-motor circuit development, the somas of motoneurons (MN) are distributed in a topographic manner in the ventral horn of the neural tube. Indeed, their position within the lateral motor columns (LMC) correlates with axonal trajectories and identity of target limb muscles. The mechanisms by which this topographic distribution is established remains poorly understood. To address this issue, we assessed the role of ephrinB2 in MN topographic organization in the developing mouse spinal cord. Results First, we used a reporter mouse line to establish the spatio-temporal expression pattern ofEfnB2 in the developing LMC. We show that early in LMC development, ephrinB2 is differentially expressed in MN of the lateral versus medial LMC, suggesting a possible role in MN sorting and/or migration. We demonstrate that while MN-specific excision ofEfnB2 did not perturb specification or migration of MN, conditional loss of ephrinB2 led to the blurring of the LMC divisional boundary and to errors in the selection of LMC axon trajectory in the limb. Conclusions Altogether, our study uncovered a novel cell autonomous role for ephrinB2 in LMC MN thus emphasizing the prevalent role of this ephrin member in maintaining cell population boundaries.